Accurate differentiation of Escherichia coli and Shigella serogroups: challenges and strategies - N.K. Devanga Ragupathi; D.P. Muthuirulandi Sethuvel; F.Y. Inbanathan; B. Veeraraghavan (New Microbes and New Infections, 2018)
Shigella spp. and Escherichia coli are closely related; both belong to the family Enterobacteriaceae. Phenotypically, Shigella spp. and E. coli share many common characteristics, yet they have separate entities in epidemiology and clinical disease, which poses a diagnostic challenge. We collated information for the best possible approach to differentiate clinically relevant E. coli from Shigella spp. We found that a molecular approach is required for confirmation. High discriminatory potential is seen with whole genome sequencing analysed for k-mers and single nucleotide polymorphism. Among these, identification using single nucleotide polymorphism is easy to perform and analyse, and it thus appears more promising. Among the nonmolecular methods, matrix-assisted desorption ionization–time of flight mass spectrometry may be applicable when data analysis is assisted with advanced analytic tools. Keywords: 16S rRNA, k-mer, MALDI-TOF MS, single nucleotide polymorphism, whole genome sequencing